Path analysis of iron and zinc contents and others traits in cowpea - Moura,Jeane de Oliveira (2012)
The objective of this study was to estimate the direct and indirect effects of agronomic and culinary traits on iron and zinc contents in 11 cowpea populations. Correlations between traits were estimated and decomposed into direct and indirect effects using path analysis. For the study populations, breeding for larger grain size, higher number of grains per pod, grain yield, reduced cooking time, and number of days to flowering can lead to decreases in the levels of iron and zinc in the grain. Genetic gains for the iron content can be obtained by direct selection for protein content by indirect effects on the number of grains per pod, 100-grain weight and grain yield. The positive direct effect of grain size and protein content on the zinc content indicates the possibility of simultaneous gain by combined selection of these traits.